2019
DOI: 10.1002/app.47932
|View full text |Cite
|
Sign up to set email alerts
|

Wet‐spinning and carbonization of graphene/PAN‐based fibers: Toward improving the properties of carbon fibers

Abstract: Graphene/polyacrylonitrile (PAN)-based composite fibers, as monofilaments, multifilaments, and yarns, were prepared through a facile solution mixing and wet-spinning method. The PAN-based (PANb) precursor was synthesized via reversible additionfragmentation chain transfer polymerization with N-isopropylacrylamide as a comonomer. Following wet-spinning, the PANb yarns were carbonized at 900 C. Scanning electron microscopy images confirmed the presence of a homogenous dispersion of graphene nanosheets inside the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 67 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…Current methods of preparing fibers mainly include melt spinning,14 wet spinning,15,16 and electrospinning 17–19. However, the presence of high temperatures and volatile solvents in the melt spinning and electrospinning processes limits the encapsulation of cells, microtissues, and other bioactive molecules in fibers 20.…”
Section: Introductionmentioning
confidence: 99%
“…Current methods of preparing fibers mainly include melt spinning,14 wet spinning,15,16 and electrospinning 17–19. However, the presence of high temperatures and volatile solvents in the melt spinning and electrospinning processes limits the encapsulation of cells, microtissues, and other bioactive molecules in fibers 20.…”
Section: Introductionmentioning
confidence: 99%
“…The comparable mechanical performance of the high-loading composite precursor to the raw PAN fiber provides a potential for manufacturing biomass-derived carbon fibers. [114], copyright 2015 American Chemical Society).…”
Section: Functional Additivesmentioning
confidence: 99%
“…Cellulose nanomaterials with high tensile strength (7.5 GPa) and modulus (110–220 GPa) have been applied as low-cost and biobased alternative reinforcements [ 114 , 115 ]. By compositing cellulose nanocrystal to the PAN matrix up to 10 wt%, Young’s modulus of the precursor fibers was increased from 14.5 to 19.6 GPa according to the rule of mixture ( Figure 13 ), and the tensile strength improved from 624 to 709 MPa owing to the microstructural changes, such as better chain alignment and crystallinity increases from 50 to 62% [ 114 ]. It was confirmed that the cellulose nanocrystal reinforcements also contributed to the advancement of the mechanical performance of carbon fibers [ 115 , 116 ].…”
Section: Functional Additivesmentioning
confidence: 99%
See 2 more Smart Citations